Raspberry Pi making amazing projects right from scratch! : explore the powers of Raspberry Pi and build your very own projects right out of the box : a course in three modules - Pajankar, Ashwin; Kakkar, Arush; Poole, Matthew; Grimmett, Richard (Packt Publishing, 2016)
Explore the powers of Raspberry Pi and build your very own projects right out of the boxAbout This Book From robotics to gaming, this Learning Path will unlock your creativity! Build your own impressive IoT projects to transform your home Featuring some of Packt's very best Raspberry Pi content, this Learning Path doesn't just get you to your destination it opens up a whole horizon of possibilities!Who This Book Is ForWant new ideas for your next Raspberry Pi project? Got one lying around gathering dust? This Learning Path gets you straight into the creative dirty work of programming and playing with your pi. Whether your new to Raspberry Pi, or an experienced maker, we think this Learning Path will inspire you and get your creative juices flowing!What You Will Learn Discover an aweome range of Raspberry Pi projects Bridge the gap between software and hardware through your Pi and find out how to make an operating system interact with cameras and other hardware Find out how to use your Raspberry Pi for gaming Secure your home with this tiny computer! Make science fiction a reality build a walking robotIn DetailLooking for inspiration for your next Raspberry Pi project? Not sure where to begin? This Learning Path is the perfect place to begin, providing you with an accessible yet comprehensive journey through Raspberry Pi. Following three modules, you'll soon be confident and prepared to get creative with your microcomputer.Raspberry Pi by Example is the first module in this Learning Path and it does exactly what it says. It doesn't just teach, it shows you how to go and build some awesome Raspberry Pi projects immediately. Build and play your own games with the Pi, build a complete Internet of Things home automation system that controls your house through Twitter... let your imagination run wild!In the next module we'll look in more depth at building a home security system. You'll be using some of the skills you devoped through the first module, but apply them to something more intricate and impressive. Using a Linux based operating system as the foundations, you'll gradually build up an entire security infrastructure adding cameras, remote controls, and even intrusion alerts!In the final module, we'll take you into the world of Raspberry Pi robotics. By the end of it, you'll have built a biped robot that can interact with its environment!This Learning Path combines some of the best that Packt has to offer in one complete, curated package. It includes content from the following Packt products: Raspberry Pi By Example by Ashwin Pajankar and Arush Kakkar Building a Home Security System with Raspberry Pi by Matthew Pole Raspberry Pi Robotics Essentials by Richard GrimmettStyle and approachIt's not every day you build a home automation system. It's not every day you build a walking robot. But with this Learning Path you'll do just that. So get started and let this tiny computer expand your imagination.
Authors: Ashwin Pajankar, Arush Kakkar, Matthew Poole, Richard Grimmett. Cf. Credits page. - Includes bibliographical references and index. - Online resource; title from title page (Safari, viewed October 11, 2016)
Keywords: Raspberry Pi (Computer) -- Programming; Python (Computer program language); Raspberry Pi (Ordinateur); Programmation; Python (Langage de programmation); COMPUTERS / Programming Languages / General; COMPUTERS / Security / General; COMPUTERS / Hardware / General